Dukungan Sosial dan Stress Reduction pada Ibu Hamil di Era Pandemi COVID-19: Studi Pendekatan Literature Review - Hery Setiawan; Hadi Pratomo; Ikrimah Nafilata; Roma Yuliana (Dian Nuswantoro Semarang, 2023)
The COVID-19 pandemic has restricted human activities or a person's mobilization. Activity restrictions can make people experience psychological disorders, including pregnant women. This certainly makes it easier for pregnant women to experience stress and the lack of direct social support by those closest to them during the pandemic. The purpose of this study is to examine social support and stress reduction for pregnant women in maintaining health during the COVID-19 pandemic era. Search literature using journal databases, namely Science Direct, Scopus, and Proquest. The journal search strategy aims to retrieve research articles that are by the research topic so that 9 journal articles are discussed in this study. The results of this research study found that social support is important for pregnant women by the closest people such as husbands, family, and friends. Social support can be provided through virtual support to improve the quality of life of pregnant women. Activities for pregnant women that can reduce stress include communicating with others, physical activity, seeking entertainment, rest, alternative therapy, nature recreation, doing home activities such as cooking, doing favorite hobbies, organizing (including studying, preparing for the arrival of the baby), and controlled eating/drinking activities.